PRINCIPAL'S ENTREPRENEURIAL COMPETENCE STRATEGY THROUGH THE UTILIZATION OF YOUTUBE SOCIAL MEDIA - Azimah, Nurul; Maryani, Maryani; Fatihin, Moh. Khoirul; Indarsari, Siti Naila; Nurmalasari, Ita (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This writing aims to transform RA Masyithoh Sutoragan into an advanced, quality, and global madrasah through the use of YouTube social media for the advancement of the institution. This arose from problems in RA, especially during the COVID-19 pandemic, where we had to hold online learning.on line. The weak ability of teachers to operate IT makes us think hard about finding a way to make learning more effective. Online learning can run smoothly. We conduct training activities independently, both online and offline, in institutions and also learn from various sources, both paid and free. The subjects of our research were teachers and education personnel at RA Masyithoh Sutoragan. The research method was carried out using a qualitative descriptive analysis method through face-to-face interviews. The results of the study show that the strategy for developing the RA head's entrepreneurial competency through the use of YouTube social media has made RA Masyithoh Sutoragan get additional income from YouTube bonuses, and RA is increasingly in demand by the community, as evidenced by the increasing number of students every year. Teachers are getting more creative. The activities and creativity of teachers are uploaded to cyberspace via YouTube, Facebook, Instagram, and TikTok.Keywords: Entrepreneurship Competence, Social Media, Youtube